Ambivalent Sexism, Attribution of Blame to the Victim and Perceptions about Victims of Violence in Relationships - Daniar Bella Amandasari; Margaretha Margaretha (ANIMA Indonesian Psychological Journal, 2019)
Female relationship violence (RV) victims often do not get help and are seen as in a negative light, even being subjected to victim-blaming, because they are triggered by sexism. Sexism, as a traditional gender perspective, puts more emphasis on the position of women; and now has an ambivalent quality, with the emergence of two forms of sexism, namely: hostile sexism (the viewing of women in a negative way, and as incompetent) and benevolent sexism (women are being considered to be weak, and so they need protection). This study aims to determine the effects of ambivalent sexism, and attributions of blame to the victims, for the perception of RV victims. The survey, conducted with on 299 students, from four high-schools in Sidoarjo, East Java, for measuring ambivalent sexism, with the Extended Ambivalent Sexism Inventory (EASI), and; the Domestic Violence Blame Scale (DVBS) to measure the attribution of blame to the victim. The perception of RV victims was measured by using a vignette which contained photos and stories about a female RV victim. Regression analysis found that benevolent sexism had a positive effect on the perceptions of victims (β = 0.19, p < .05). Individuals demonstrating high benevolent sexism will tend to view KDP RV victims as traditional women.